Sequence Paleogeography of the Middle Jurassic Shimengou Formation in the Yuka Area - Tong, Yue (International Journal of Natural Resources and Environmental Studies, 2026)
To investigate in detail the evolution characteristics of lithofacies and sedimentary facies belts within a sequence stratigraphic framework, the sequence stratigraphic framework of the lower member of the Shimengou Formation in the Yuka area was established based on field drilling core descriptions. Single-factor isoline maps were drawn according to systems tracts, and the lithofacies paleogeography was reconstructed.